Coastal tourism through a Muslim women’s gaze: insights from Malaysia - Asbollah, Asra Zaliza; Zakariya, Khalilah; Mansor, Mazlina; Amit, Hadezah (Malaysian Institute of Planners (MIP), 2025)
Tourism is not only a movement of people but also a socially constructed way of seeing shaped by culture, religion, and gender. Coastal tourism is often associated with open bodily display and carefree leisure, which may conflict with Muslim women’s expectations of modesty, safety, and family orientation. While Malaysia positions itself as a leading Muslim-friendly destination, limited research has centred Muslim women’s voices in beach-based tourism. This study addresses this gap by applying and extending Urry’s tourist gaze theory through the development of a Muslim Women’s Tourist Gaze Framework (MWTG). Using a qualitative, interpretive single-case design, Port Dickson (PD) was studied through 25 semi-structured interviews with Muslim women tourists and key stakeholders, supported by on-site observations. Thematic analysis revealed that women’s coastal experiences are organized around three interlinked logics: (1) ethical-spiritual, viewing nature as a site of gratitude and reflection; (2) family-collective, prioritizing safety, modesty, and kinship roles; and (3) environmental stewardship, valuing cleanliness and preservation. Findings extend the tourist gaze beyond Eurocentric assumptions by embedding faith, family, and ecological care into coastal leisure. Practically, the study highlights the importance of modesty-supportive infrastructure, halal assurance, and sustainability in strengthening Malaysia’s coastal tourism appeal.